1996
DOI: 10.1111/j.1744-7348.1996.tb07328.x
|View full text |Cite
|
Sign up to set email alerts
|

A review of the pre‐oviposition behaviour of small cabbage white butterfly, Pieris rapae(lepidoptera: Pieridae)

Abstract: This paper reviews the literature concerning the ovipositional behaviour of Pieris r a p e (small cabbage white butterfly) and where appropriate considers results from studies involving other butterflies. The paper considers searching behaviour , stimuli utilised in host plant finding and identification and concludes with a general section on the role of learning and prior experience in ovipositional behaviour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 95 publications
2
54
0
Order By: Relevance
“…Alternatively, it is possible that females are plastically altering dispersal strategies depending on the quality of their larval diet, which has been seen in other species of butterflies (53,54). If females reared on higher-sodium diets perceive these resources as higher quality, it may pay to invest less in flight and dispersal and instead, invest more in searching locally (55,56). However, experiments are needed to determine whether the pattern in females is adaptive or simply a stress response.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, it is possible that females are plastically altering dispersal strategies depending on the quality of their larval diet, which has been seen in other species of butterflies (53,54). If females reared on higher-sodium diets perceive these resources as higher quality, it may pay to invest less in flight and dispersal and instead, invest more in searching locally (55,56). However, experiments are needed to determine whether the pattern in females is adaptive or simply a stress response.…”
Section: Discussionmentioning
confidence: 99%
“…De Vos et al (2008) showed that ovipositing P. rapae preferred isothiocyanate-producing Arabidopsis Col-0 plants over 35S:ESP plants, even when the plants were not damaged. Numerous studies have shown that the nonvolatile glucosinolates serve as oviposition stimulants for P. rapae and closely related species (overview given by Chew and Renwick 1995;Hern et al 1996;Schoonhoven et al 2005). However, given that most glucosinolate hydrolysis products are volatile, while the parent glucosinolates are not, the hydrolysis products might be important cues for P. rapae at an earlier stage of the host location process.…”
Section: Discussionmentioning
confidence: 99%
“…P. rapae is a cosmopolitan species, which is widespread throughout Europe, Asia and North America. The damage to foliage caused by P. rapae is slight, although it can be severe in seasons with a high infestation of caterpillars (Hern et al, 1996). P. napi is spread throughout the northern hemisphere ranging from North America, Europe and Asia to North Africa.…”
Section: The Cabbage White Butterflies (Pieris Brassicae Pieris Rapamentioning
confidence: 99%
“…Among the four different crucifer-specific compounds tested towards perception of P. rapae, phenylacetonitrile elicited a higher response than ally1 isothiocyanate, benzyl isothiocyanate and 2-phenylethyl isothiocyanate (Hern et al, 1996). Furthermore, P. rapae is considered to be an important pollinator for many plant species, since the butterfly occurs three to four times a year and tends to visit a diversity of flowers (Ômura et al, 1999).…”
Section: Host Plants (Brassica Spp)-herbivores (Pieris Spp)-parasitmentioning
confidence: 99%